2022
DOI: 10.4028/p-24y9ae
|View full text |Cite
|
Sign up to set email alerts
|

Modeling of High Module Power Sources Systems Safety Processes

Abstract: The paper provides an assessment of the safety processes of high-modulus energy sources systems during the initiation of flat and cylindrical high-modulus energy sources. The expressions, which establish the relationship between the parameters of flat and hollow cylindrical charges of explosives under the only condition of equality of the developed pressure pulse on the surface of the charge of explosives, provided all other things being equal, were obtained. In contrast to the earlier studies, which assert th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…The results of the analysis of errors in programs [9], [10] showed that complex software cannot exist in an absolutely debugged state. Errors [11][12][13] introduced into programs during design, development, and implementation are sources of software reliability degradation. At the stage of structural design, errors in determining the structure of programs are possible.…”
Section: Fig 2 List Of the Most Active Extortion Groupsmentioning
confidence: 99%
“…The results of the analysis of errors in programs [9], [10] showed that complex software cannot exist in an absolutely debugged state. Errors [11][12][13] introduced into programs during design, development, and implementation are sources of software reliability degradation. At the stage of structural design, errors in determining the structure of programs are possible.…”
Section: Fig 2 List Of the Most Active Extortion Groupsmentioning
confidence: 99%